Conducting Concerti : A Technical and Interpretive Guide - Itkin, David (Book collections on Project MUSE., 2014)
This book examines 43 great concerti and discusses, in detail, the technical, aural, rehearsal, and intra-personal skills that are required for ""effortless excellence."" Maestro Itkin wrote this book for conductors first encountering the concerto repertoire and for those wishing to improve their skills about this important, and often understudied, literature. Often misunderstood is the fact that both the physical technique and the score study process require a substantially different and more nuanced approach than with the major symphonic repertoire. In short, this is the book that Itkin wis